Transumbilical single-port laparoscopic cholecystectomy using traditional laparoscopic instruments: a report of thirty-six cases - Cao, Li-ping (Zhejiang University Press, 2011)
Objective: To evaluate the feasibility and safety of the operation of transumbilical single-port laparoscopic cholecystectomy (TSPLC) by traditional laparoscopic instruments and summarize the initial experience. Methods: Sixty subjects with cholelithiasis were divided into two groups. One group (36 cases) underwent TSPLC and the control group (24 cases) underwent traditional three-port laparoscopic cholecystectomy (LC). Postoperative complications were observed and operation time, hospital days, visual analogue scale (VAS) after 6 and 24 h of operation, and subject satisfaction score were measured. Results: TSPLC and traditional LC were performed successfully in the two groups. The operation time in the TSPLC group was significantly longer than that in the control group. There was no statistically significant difference in hospital stay and VAS between the TSPLC and control groups. The subject satisfaction score in the TSPLC group was 91.2, significantly higher than that in the control group (P<0.01). All subjects recovered from the operation and no postoperative complication occurred during the period of two weeks after operation. Conclusions: TSPLC is a feasible and safe method for cholecystectomy, although it may be more time-consuming. However, it is welcomed by patients who are more concerned with cosmetic outcomes. Future studies are needed to confirm its disadvantages and contraindications.